Forage seed multiplication by ILCA - Griffiths, B. (Australian Centre for International Agricultural Research, 1990)
Gives an introduction to the sub-Saharan Africa seed scene together with details of the seed units proposed activities. Outlines objectives of the Forage Seed Unit. Discusses small scale seed multiplication of seeds for the genebank and large scale multiplication of seeds by the seed unit.